2021
DOI: 10.1016/j.jpeds.2020.12.057
|View full text |Cite
|
Sign up to set email alerts
|

Association between Baseline Cortisol Serum Concentrations and the Effect of Prophylactic Hydrocortisone in Extremely Preterm Infants

Abstract: for the PREMILOC Trial Study Group* Objective To define nomograms of serum cortisol values before 24 hours of postnatal life for extremely preterm infants and determine whether baseline cortisol values affect the benefit/risk ratio of prophylactic hydrocortisone to improve survival without bronchopulmonary dysplasia (BPD). Study designWe performed a predefined secondary analysis of the multicenter randomized controlled PREMI-LOC trial that included inborn infants delivered before 28 weeks of gestation. Nomogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…This observed duration of action of antenatal steroids lends support to our observation of higher SIP risk when antenatal steroids exposure was more recent, as there may be inadequate time for the intestinal mucosa to recover. In a secondary analysis of a recent multicenter randomized controlled trial including infants <28 weeks of gestational age at birth, Renolleau et al 21 Table II…”
Section: Table I Maternal and Infant Baseline Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…This observed duration of action of antenatal steroids lends support to our observation of higher SIP risk when antenatal steroids exposure was more recent, as there may be inadequate time for the intestinal mucosa to recover. In a secondary analysis of a recent multicenter randomized controlled trial including infants <28 weeks of gestational age at birth, Renolleau et al 21 Table II…”
Section: Table I Maternal and Infant Baseline Characteristicsmentioning
confidence: 99%
“…19,20 A secondary analyses from a recent trial revealed that higher cortisol levels after birth were associated with higher odds of SIP in infants who received postnatal hydrocortisone. 21 Exposure to antenatal steroids and prophylactic indomethacin was postulated to be associated with SIP. 22 A previous study did not find an association between antenatal steroids and SIP, whether alone or in combination with prophylactic indomethacin, 23 but it lacked data on the timing of antenatal steroids.…”
mentioning
confidence: 99%
“…Some centres have already adopted routine early hydrocortisone supplementation to improve perinatal outcomes. However, early routine hydrocortisone may have negative interaction with potential high levels of endogenous cortisol (if not measured), which may increase the risk of severe IVH and spontaneous intestinal perforation [164]. Hydrocortisone prophylaxis seems promising, but more work is required before it is routinely adopted for all preterm infants, especially those below 26 weeks of gestation [165].…”
Section: Introductionmentioning
confidence: 99%
“…5 In this volume of The Journal, Renolleau et al add new relevant information on the benefit-risk strategy concerning BPD treatment with early systemic steroids. 6 The use of systemic steroids as treatment of BPD started almost 30 years ago after the publication of a study by Mammel et al 7 This small randomized, blinded study showed a benefit of dexamethasone in the treatment of BPD. Although authors recommended further studies on possible long-term side effects, the use of dexamethasone for BPD became common practice for many years thereafter.…”
mentioning
confidence: 99%
“…In this volume of The Journal, Renolleau et al explored whether the benefit-risk ratio of early low-dose hydrocortisone could be improved when baseline cortisol levels before treatment were taken into account. 6 In a first step, they created sex-adjusted nomograms of serum cortisol levels on the first day of life and calculated sex-adapted cortisol z scores. The authors succeed in providing us reliable, reproducible baseline cortisol values while including the greatest number of infants born extremely preterm ever assessed.…”
mentioning
confidence: 99%